1357 nm passively Q-switched crystalline ceramic laser based on multilayer graphene. (13th April 2016) - Feng, Chao; Zhang, Huanian; Wang, Qingpu; Xu, Shicai; Fang, Jiaxiong
Abstract: 1357 nm single wavelength passively Q-switched Nd:YAG ceramic lasers are demonstrated with a multilayer graphene sheets saturable absorber (SA). During an increase in the incident pump power, the laser exhibited stable Q-switched oscillation, which showed that our graphene SA provided Q-switched modulation successfully. The maximum average output power was 340 mW, and the corresponding pulse width, pulse repetition rate, single pulse energy and peak power were 380 ns, 209 kHz, 53 μ J and 139 W, respectively. Our results illustrate that graphene can be used as an SA for 1357 nm passively Q-switched Nd:YAG ceramic lasers.